2014
DOI: 10.21273/hortsci.49.10.1268
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalin Content in Kernels of Several Almond Cultivars Grown in Turkey

Abstract: Amygdalin is a bioactive compound used in the traditional treatment of some diseases, and it is toxic to humans and animals when it is consumed excessively. It is abundantly found in the kernels of almond cultivars, especially in bitter ones. In the study, the amygdalin contents of the kernels of 15 commercial almond cultivars (Prunus amygdalus L.) were determined by high-performance liquid chromatography (HPLC) for 2 consecutive years. The seeds of the cultivars were obtaine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The results on amygdalin content in almond explained that the bitter varieties had a higher amount of amygdalin much more than semi-bitter and sweet variety (Sánchez-Pérez et al 2008;Lee et al 2013;Yildirim et al 2014). Our results were consistent with the abovementioned research.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The results on amygdalin content in almond explained that the bitter varieties had a higher amount of amygdalin much more than semi-bitter and sweet variety (Sánchez-Pérez et al 2008;Lee et al 2013;Yildirim et al 2014). Our results were consistent with the abovementioned research.…”
Section: Discussionsupporting
confidence: 91%
“…The highest amount of amygdalin was recorded for slightly bitter (25 mg/100 g DW) and bitter cultivars from 2400 to 6000 mg/100 g DW (Arrázola et al 2012). Yildirim et al (2014) reported that amygdalin content varied among almond cultivars so that the higher amount was recorded in some sweet cultivars than in light bitter specimens. Also, they reported amygdalin range from 37 to 145.8 mg/100 g DW in Masbovera sweet cultivar and Supernova light bitter cultivar, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As kernels of almonds, apricot, plums, peaches, apples and other members of the Rosaceae family are known for containing a toxic cyanogenic glycoside called amygdalin ( Bolarinwa et al, 2014 , Yildirim et al, 2014 ), which is hydrolyzed by β-glucosidase into hydrogen cyanide (HCN), benzaldehyde and d-glucose ( Walker and Krieble, 1909 ). The toxicity of HCN is due to cyanide ion, which stops bacterial cellular respiration by inhibiting cytochrome C oxidase enzyme located in the bacterial membranes ( Organization for the Prohibition of Chemical Weapons, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although not as popular as them, apricot kernel is the by-product of one of the most produced fruits in temperate areas (Gómez et al, 1998). The main issue about apricot kernel seed and oil use is the presence of amygdalin (Akinci Yildirim and Atilla Askin, 2010). This can be easily solved by using a sweet variety that contains a small quantity of it, compared to the bitter one (Gorrepati et al, 2015).…”
Section: Introductionmentioning
confidence: 99%